Industrial training report: Ban Chu Bee Honda Sdn. Bhd. / Nur Natasha Adieba Mat Nashim - Mat Nashim, Nur Natasha Adieba (Faculty of Business and Management, 2025)
Following the 12 august 2024, I have to finish my studies with the last semester which is semester 6 by undergoing an internship. The subject for semester 6 is MGT666 named Internship. Every student has to choose one of the companies to undergo an internship. The company I have chosen is Ban Chu Bee Honda Sdn Bhd in Pasir Mas, Kelantan. Ban Chu Bee Honda Sdn Bhd is the largest and main Honda dealer in Kelantan. I have learned a lot since I did my internship at this company. One of the new lessons I got was how to interact with customers. Furthermore, as we know, customers' attitudes are different and we as customer relations executives need to treat them with competence and professionalism. During my internship at Ban Chu Bee Honda, even though this is my first time in a company that is based on the automotive industry, I was not impressed not to increase my knowledge, here, I can improve my communication skills with customers, I can also explain a little about the problems that customers ask. Through my experience at BCB, I was able to understand the importance of effective communication and relationship between customer service and consumers in the automobile sector. Furthermore, I witnessed how BCB managed to overcome challenges that come to the company and handled it in good ways. In addition to broadening my understanding of the automotive industry, this internship helped me in developing important abilities such as flexibility, problem solving and teamwork. Being a company that trying to grow in a competitive market gave me an understanding of the determination and creativity required to succeed in the field. With a strong background in dealership operations and customer interaction, my experience at Honda BCB has prepared me to contribute successfully in the future.